PENGARUH KUALITAS DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA PARIS DAY HOTEL PAMANUKAN - Udin Zaenudin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Service companies must be able to design appropriate marketing strategies in achieving company goals, one of the company's goals is to create customer loyalty. This study aims to determine whether the variables Quality and Customer Satisfaction significantly influence Customer Loyalty at Paris Day Hotel Pamanukan and to determine the variables that influence between the two variables Quality and Customer Satisfaction on Customer Loyalty at Paris Day Hotel Pamanukan. The sample used the Purposive Sampling method, namely by directly selecting all 50 employees. The data collection method used was direct interviews with the parties involved with the issues being discussed and giving questionnaires to hotel customers in accordance with the research conducted. The analysis tool used is Multiple Linear Regression Analysis. The results showed that together (simultaneously) the Fcount value was 11.554 and the Sig value 0.000 was smaller than 0.05 which means Quality and Customer Satisfaction had a significant effect on Customer Loyalty at Paris Day Hotel Pamanukan. Variable Quality and Customer Satisfaction regression coefficient is positive (+) indicating a unidirectional relationship, in other words Quality and Customer Satisfaction will increase Customer Loyalty at Paris Day Hotel Pamanukan Correlation or relationship between Quality and Customer Satisfaction with Customer Loyalty Paris Day Hotel Pamanukan is very strong of (r = 0.574) and the coefficient of determination or the R square number is 0.330. Based on the results and discussion that has been done, it can be interpreted that quality and satisfaction affect customer loyalty at Paris Day Hotel Pamanukan. Therefore Ho is rejected.